(untitled) - Zuniga, Joaquin Martinez De (Manila, 1966)
The need for a concise and compact history of the Philippines was felt a century and a half ago. At least half dozen thick volumes had been written on the subject, but with one exception they had been written by frairs who were more interested in relating the chronicles of their respective monastic orders than in a history of the events and important personages of that colony.